Гендерні особливості англомовної Інтернет-комунікації - Воротняк, Л. (Філологічний дискурс, 2020)
У статті виявлено та проаналізовано основні гендерні
характеристики англомовної мережевої комунікації. Встановлено,
що мережева комунікація має ґендерну маркованість, яка
виражається у приналежності до категорій фемінності та
маскулінності. Диферентні особливості чоловічої та жіночої
мережевої комунікації проявляються на лексичному, фонетичному,
стилістичному та синтаксичному рівнях. The article identifies and analyzes the main gender characteristics of Englishlanguage
network communication. Scientists argue that there are some differences
between male and female communication. Therefore, it is advisable to consider the
peculiarities of the speech style of men and women. There are two basic concepts in gender linguistic research – sex and gender,
which are often mistakenly used synonymously. Sex is a set of anatomical and
physiological features of a person. Gender is also interpreted as a specific set of
cultural characteristics that determine the social behavior of men and women and
their relationships. In linguistics, gender is seen as a cognitive phenomenon that
manifests itself in the cliché as well as in the peculiarities of communicative speech
behavior. It has been established that network communication has a gender-based mark,
which is expressed in terms of categories of femininity and masculinity. The verbal
behavior of English-speaking Internet users clearly shows gender differences.
Differential features of male and female network communication are manifested at
the lexical, phonetic, stylistic and syntactic levels. Men’s verbal behavior is characterized by accuracy, stylistically neutral
vocabulary, concise and less dynamic texts, clarity, directness, informativeness,
unambiguity, the use of terms, slang and profanity, construction of simple sentences
etc. Women have the following features: hyperbolized expressiveness, verbosity, use of
exclamation points and divisive questions, the conversation is moderately polite.